Word journeys assessment-guided phonics, spelling, and vocabulary instruction - Ganske, Kathy (2014)
"This trusted teacher resource and course text provides a comprehensive approach to assessing and building children's word knowledge (grades K-8). Kathy Ganske shows how carefully planned word study can improve students' reading and writing skills while fostering their appreciation of language. Complete instructions are provided for implementing the Developmental Spelling Analysis (DSA), an easy-to-use assessment tool, and for tailoring instruction to learners' strengths and weaknesses. Numerous word lists, student work samples, and "Literature Links" are included, along with 24 reproducible forms. The large-size format facilitates photocopying. Purchasers also get access to a Web page where they can download and print the reproducible materials"
Machine generated contents note: I. Understanding Word Study Contexts -- 1. Word Study: Reading, Writing, and Language Connections -- II. Understanding Children's Word Knowledge -- 2. A Developmental Perspective -- 3. Assessing Word Knowledge: The Developmental Spelling Analysis -- III. Fostering Children's Word Knowledge -- 4. Planning Appropriate and Engaging Instruction -- 5. Letter Name Word Study -- 6. Within Word Pattern Word Study -- 7. Syllable Juncture Word Study -- 8. Derivational Constancy Word Study -- 9. Questions and Answers -- Appendix 1. Supplemental Word Lists -- Appendix 2. Reproducible Forms -- Resources -- Glossary.
MFO Aquino (Recommending faculty) AY2016-2017
Includes bibliographical references and index.
Keywords: Vocabulary -- Study and teaching; English language -- Orthography and spelling -- Study and teaching; Reading -- Phonetic method; LANGUAGE ARTS & DISCIPLINES / Literacy; EDUCATION / Teaching Methods & Materials / Reading & Phonics; EDUCATION / Elementary; LANGUAGE ARTS & DISCIPLINES / Reading Skills